Actions for Bioenergy and Biofuels: A Sustainable Shift - D'Adamo, Idiano; Morone, Piergiuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The topic of bioenergy is a multidisciplinary one, where the use of resources and skills can be optimized for the development of sustainable models. It is a time for green strategies, but also for action. It is, therefore, necessary to implement projects that address virtuous examples of the circular bioeconomy. All politicians are called on to contribute, because this global goal can only be achieved if a contribution is made by all countries.